Sistem E-Commerce Penjualan Ikan - Risna Sri Nanda Kurnia Kurnia (STKIP Taman Siswa Bima, 2024)
Selling fish is a business with a long history. With the advancement of technology, digital transformation has become something that cannot be ignored. Fish are usually sold through traditional methods, such as direct sales to stores, direct sales to fish sales contributors or direct sales to traditional markets. However, with the rapid development of the times, it is very important to achieve online sales of fish sales. Therefore, developing online fish sales is important, because it will make it easier for sellers to inform or market their fish more widely, manage fish stocks, report fish sales and make it easier for customers to search for products or ask about fish sales. In developing this system, a system development method is required, namely using the SDLC (System Development Life Cycle) method, more precisely the agile method, namely a method or framework that is incremental, iterative and market-based in a dynamic and dynamic manner. quickly adapt to customer needs. Therefore, the development of online fish sales is very important as it makes it easier for sellers to better inform or market their fish more widely, manage fish stocks, report fish sales, and makes it easier for customers to search for products or Search for fish sales questions. When developing this system, a system development method is needed, that is, using the SDLC method (System Development Life Cycle), more precisely the agile method, which is a market-based, dynamic, incremental, and iterative method. method or framework. dynamic way. Quickly adapt to customer needs. ABSTRAK Penjualan ikan merupakan salah satu bisnis yang sudah ada sejak dahulu kala, dengan kemajuan teknologi, transformasi digital menjadi hal yang tidak bisa dihindari. Dalam proses penjualan ikan biasanya dilakukan melalui metode konvensional, seperti penjualan langsung ke toko-toko, penjualan langsung ke orang yang berkontribusi mengenai penjualan ikan atau penjualan langsung ke pasar tradisional. Namun dengan perkembangan zaman yang semakin pesat, penting adanya transformasi dengan penjualan ikan yang memungkinkan menjual ikan secara online. Oleh karena itu pengembangan penjualan ikan berbasis online penting dilakukan, karena akan mempermudah penjual untuk menginformasikan atau memasarkan ikannya lebih luas, manajemen stok ikan, pelaporan penjualan ikan dan mempermudah costumer untuk melakukan pencarian produk atau menanyakan mengenai penjualan ikan. Dalam mengembangkan sistem ini diperlukan suatu metode pengembangan sistem yaitu dengan menggunakan metode SDLC (System Development Life Cycle), lebih tepatnya metode agile yaitu suatu metode atau kerangka kerja yang bersifat inkremental, iteratif, dan berbasiskan pasar secara dinamis dan dinamis. cepat menyesuaikan dengan kebutuhan pelanggan.